AKSESIBILITAS MASA PANDEMI COVID-19 BAGI DIFABEL NETRA DI PERPUSTAKAAN MARDI WUTO YOGYAKARTA - Sari, Khairunnisa Etika (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
This research discusses the accessibility for people with visual impairments in using libraries during the Covid-19 pandemic. The formulation of the problem in this study is that the reality of the blind with disabilities when they need information in the library will be different to with the times before the pandemic. Researchers try to describe how a library imposes regulations on accessibility for persons with visual disabilities who visit and need access to the library safely and comfortably. This research is a field research with the method used is qualitative research methods. To get information about this research, researchers used the method of involved observation, in-depth interviews, and documentation methods. The results of the study showed that Mardi Waluyo Library when Covid-19, effectively carried out activities to facilitate access for blind people with disabilities, including: transfer of digital collections, online services, intensive collaboration, rearranging rooms, limiting visits and education on prevention and Covid-19 virus transmission.